HUBUNGAN DISIPLIN KERJA DAN IMBALAN DENGAN KEBERHASILAN TUGAS GURU SEKOLAH MENENGAH KEJURUAN (SMK) SE-KECAMATAN SEPUTIH BANYAK KABUPATEN LAMPUNG TENGAH - Temu, Temu (JURNAL LENTERA [PENDIDIKAN PUSAT PENELITIAN LPPM UM METRO], 2018)
The success of the teacher's  relatioship by the factors: the discipline of work, remuneration. School management should understand that both these aspects become contributors to the success of a teacher in managing learning. This study aimed to analyze: (1) the relationship between the discipline of work by the success of the task of teachers, (2) the relationship between remuneration to the success of the task of the teacher, and (3) the relationship between the discipline of work and remuneration together with the success of the task of teachers. This study population of teachers SMK-District of Central Lampung regency Many white as many as 83 teachers are used as the study sample as many as 69 teachers using the formula slovin and for testing using correlation as a tool. From the results of the hypothesis can be seen that: The relationship of labor discipline variable to variable teacher assignment success. Significance of test results obtained scores probability (sig) of 0.000 with a regression coefficient of 6.2% is significant or regression model can be used to predict the success of the task of the teacher is a portrait of the meaningfulness of work discipline variable relationship to the variable success of the task of the teacher is very significant, the relationship between variable remuneration to the success of the task of teachers.